EXAMINING THE IMPACT OF SINGLE PARENTING ON THE ACADEMIC PERFORMANCE OF JUNIOR HIGH SCHOOL STUDENTS - Aubrae Frances Engngeg Bannawi; Novia Praise Dewanan Foy-awen; Amir Sam Tagtag Joseph; Glayrheal Ducas Del Rosario; Lester Lyle Dayasen Andawi; Nover Luke Dalog Eslao; Ashlyn Jace Lagasca Banih; John Rey Osben Pelila, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aimed at knowing the relationship between single parenting, particularly the level of involvement of single parents, and the academic performance of their children who are in high school level. The study employed a quantitative method, specifically a correlational design, and through purposive sampling, 42 Junior High School (JHS) respondents were surveyed in one of the diocese schools in Baguio-Benguet. The researchers used a survey questionnaire to gather data; all the information was statistically analyzed using descriptive statistics and the Pearson correlation coefficient. Based on the findings, it was found that single parents had a high level of involvement in terms of giving words of wisdom or moral support but not in physical actions, particularly in attending school activities. However, the respondents showed good academic performances based on their satisfactory grades. Nevertheless, it was revealed that there was a weak negative correlation between single parenting and the academic performances of the respondents. Therefore, it is imperative to note that too much meddling by single parents with their children can lower their academic performances.